PRESPEKTIF HADIS DALAM ELEKTABILITAS WANITA DALAM POLITK AKTIF STUDI KOMPARASI DAN SOLUSI - Fadhilah Is (SHAHIH (Jurnal Ilmu Kewahyuan), 2019)
The Ulama are divided into three groups in understanding and interpreting the hadith (that will not be lucky for a people when led by women). Among them there are those who cover all gaps and prohibit women's participation in the political world, some of them allow women to be active in politics unless they become the supreme leader of the country, and the latter group absolutely allows even the highest leadership in a country. The perspective of the writer after analyzing and studying in the understanding of this hadith is more inclined to the second opinion, that is, it is permissible for women to be active in politics in general not as the highest leader in a country, but for those who can fulfill the following conditions; The work is indeed advised. This means that it is not illegitimate work or brings to illegitimate matters; Maintain a Muslim woman when she leaves her house, by maintaining how to dress, walk, talk, and even move; The work is in accordance with the nature and nature of women; His work did not neglect his main obligations, such as the obligation to take care of his husband and children. Because that's the most important job for a woman